A double blind placebo controlled trial of medroxyprogesterone acetate (MPA) in cancer cachexia. - Downer, S. (1993)
Patients with breast cancer treated with MPA often report an improvement in appetite. Similar appetite stimulation is seen in patients treated with some corticosteroids, but MPA has a potential advantage over these drugs in that it does not exert a catabolic effect. MPA (100 mg tds orally) has therefore been compared with placebo in 60 patients with advanced malignant disease. Twenty-one patients in the MPA group and 20 in the placebo group were receiving chemotherapy. Patients were treated for 6 weeks and were assessed at weeks 0, 3 and 6 for appetite, energy, mood and pain using visual analogue scales. Nutritional status was assessed by the measurement of serum proteins and anthropometrics. Karnofsky score was recorded as a measure of performance status. There was a significant improvement in appetite in the MPA group between weeks 0 (pre-study) and 3 (P = 0.0002) and 0 and 6 (P = 0.015). There was no significant improvement in appetite in the placebo group. Supporting this finding was the significant increase in serum thyroid binding pre-albumin and retinol binding protein in the MPA group between weeks 0 and 3 and 0 and 6 (P = 0.023 and P = 0.039 respectively). These two parameters showed no significant change in the placebo group. There was no change in anthropometric measurements, weight, performance status, energy, mood or pain in either group. These data indicate that there was a significant increase in appetite in anorexic patients with advanced cancer treated with MPA which was reflected in increases in rapid turnover proteins reported to reflect nutritional status. However, this apparent increase in appetite did not result in improved weight, performance status, energy levels, mood or relief of pain. Further studies to investigate the effect of higher doses of MPA are indicated.